On mixture periodic Integer-Valued ARCH models. Issue 12 (2nd December 2021) - Ouzzani, Fares; Bentarzi, Mohamed
Abstract: This paper deals with the study of Mixture Periodic Integer-Valued Autoregressive Conditionally Heteroskedastic models. Some theoretical properties of the model, such as the first and the second moment periodically stationary conditions, are established. Moreover, closed-forms of these moments are, under these conditions, derived. The estimation is done by the maximum likelihood via the iterative EM algorithm and the performance of this method is shown via an intensive simulation study. A comparative real data study is performed on a Campylobacteriosis time series.